(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This project’s aim is to use Arduino Board technology to create measurements of solar energy. Temperature, light, voltage, and current and the four parameters are measured in this analysis. The temperature sensor is used to measure temperature. The intensity of light is calculated using a LDR sensor. Since the voltage provided by the solar panel is too high to be used as a receiver for the Arduino, a voltage divider was used to determine the voltage. Finally, acs712 module was used to calculate the current, which can detect the current generated by the solar panel. These parameters were shown on the LCD screen as the Arduino’s input and output values. The values are all displayed on the LCD panel and mobile phone through the cloud. Arduino’s goal is to convert the parameter’s analog input to a digital output and display it on an LCD, as well as on a smartphone. Aside from that, this project often involves a plan that ensure the device case is easy.